2021
DOI: 10.3389/fimmu.2021.718246
|View full text |Cite
|
Sign up to set email alerts
|

PADI2 Polymorphisms Are Significantly Associated With Rheumatoid Arthritis, Autoantibodies Serologic Status and Joint Damage in Women from Southern Mexico

Abstract: The enzymes of the family peptidylarginine deiminases (PADs) have an important role in the pathogenesis of rheumatoid arthritis (RA) due to their association with the anti-citrullinated protein antibodies (ACPA) production. To evaluate the association between single-nucleotide polymorphisms (SNPs) in the PADI2 gene and RA susceptibility, related clinical parameters, and the serologic status of autoantibodies in a women population with RA from southern Mexico, a case-control study was conducted (case n=229; con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Among the transcription factors, SPI1 , PADI2 , ZNF366 and CBFA2T3 were in the top ten transcription factors for hub score, betweenness centrality and out-degrees for all the comparisons. Polymorphisms in the PADI2 genes are associated with RA [ 33 , 34 ]. Its role in circulating CD4 + T cells of RA patients is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Among the transcription factors, SPI1 , PADI2 , ZNF366 and CBFA2T3 were in the top ten transcription factors for hub score, betweenness centrality and out-degrees for all the comparisons. Polymorphisms in the PADI2 genes are associated with RA [ 33 , 34 ]. Its role in circulating CD4 + T cells of RA patients is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In RA diagnosis, composite scores of disease activity, such as the DAS-28 (including tender joint count (TJC) and swollen joint count (SJC)), along with the measurement of ESR, CRP level, and general health (GH) status are of importance in evaluating RA treatment response. However, the assessment of these parameters in groups of patients may not be as accurate as that in individual patients [ 34 ]. In the present study, patients with RA exhibited high disease activity with a moderately elevated inflammatory condition based on the DAS-28, ESR, and GH status, whereas the CRP level remained normal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anti-CEP was notably associated with the PADI2 SNP rs1005753 ( **p < 0.01). Moreover, PADI2 has been found to be a candidate gene in RA progression, and its high expression has been observed in the synovial fluid of patients with RA, correlating with inflammatory markers and clinical activity of the disease [ [46] , [47] , [48] ]. In addition, Too et al identified a novel association between the PADI2 genetic variant rs1005753 and RA in a multiethnic population from Southeast Asia [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This causes the destruction of cartilage and the aggravation of RA ( 94 ). Furthermore, individual genetic polymorphisms of PADI2 and PADI4 can increase susceptibility to RA ( 35 37 , 41 , 43 , 46 , 47 , 95 97 ). In ACPA RA, PADI4 can help HLA-DRB1 bind to ACPA ( 98 , 99 ).…”
Section: The Padi Family and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%